Normeringen i Finlandssvensk ordbok - af Hällström, Charlotta (LexicoNordica, 2002)
Finland Swedish is a variety of Swedish, not a separate language. The aim of Finland- Swedish language planning is among other things that the Finland Swedish will endure as a variety of the Swedish language. One of the means is Finlandssvensk ordbok (’Finland Swedish Dictionary’; af Hällström & Reuter 2000) which in a way is a both normative and descriptive dictionary. The readers are adviced against using some of the so called finlandisms, whereas other finlandisms are accepted in some contexts. In this article the author explains the principles of the norms in Finlandssvensk ordbok.